Rules of exception and guarantee of rights in times of pandemic - Carrillo López, Marc (Journal of the Basque Parliament, 2020)
The COVID-19 pandemic has been a challenge for the rule of law. The application of the rule of exception regulated in the Constitution has introduced restrictions on fundamental rights in order to protect the health of citizens. This study examines the scope and limits of the state of alarm in Spain, as one of the three forms of the rule of exception provided for in the Constitution and Organic Law 4/1981, which allows facing the challenge of the pandemic without the suspension of fundamental rights being necessary. From this perspective, the impact of the emergency measures adopted by the Government on the exercise of some fundamental rights and the judicial response to the appeals presented by citizens is analyzed, especially with respect to freedom of movement and the right to demonstrate, in addition of freedom of expression especially through social networks, and the guarantee of the right to habeas data. In all these cases, the application of the proportionality test is examined to assess the exercise and limits of public power in the application of the measures designed to guarantee public health and its impact on these fundamental rights.